Interplay between cancer-associated fibroblasts and dendritic cells: implications for tumor immunity - Fátima María Mentucci; María Gracia Ferrara; Agustina Ercole; Natalia Belén Rumie Vittar; Natalia Belén Rumie Vittar; María Julia Lamberti; María Julia Lamberti (Frontiers in Immunology)
The tumor microenvironment (TME) plays a critical role in cancer progression, with cancer-associated fibroblasts (CAFs) emerging as key players in immune evasion. This review explores the complex interactions between CAFs and dendritic cells (DCs), essential antigen-presenting cells that activate immune responses. CAFs impair DC maturation and function by secreting cytokines, chemokines, and growth factors, reducing their ability to present antigens and stimulate T cells, thus promoting an immunosuppressive environment favorable to tumor growth. Additionally, CAFs contribute to the differentiation of tolerogenic DCs, fostering regulatory T cells (Tregs) that further suppress antitumor immunity. This review examines the molecular mechanisms underlying CAF-DC crosstalk and discusses potential therapeutic strategies aimed at restoring DC functionality. Targeting the CAF-driven immunosuppressive network offers promising opportunities to enhance the efficacy of DC-based vaccines and immunotherapies, paving the way for improved cancer treatment outcomes.